Modeling the impact of jamming attacks in the internet of things - Imane Kerrakchou; Sara Chadli; Yassine Ayachi; Mohammed Saber (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Security is a key requirement in the context of the Internet of Things. The IoT is connecting many objects together via wireless and wired connections with the goal of allowing ubiquitous interaction, where all components may communicate with others without constraints. The wireless sensor network is one of the most essential elements of IoT concepts. Because of their unattended and radio-shared nature for communication, security is becoming an important issue. Wireless sensor nodes are susceptible to different types of attacks. Such attacks can be carried out in several various ways. One of the most commonly utilized methods is Jamming. However, there are also some other attack types that we need to be aware of, such as Tampering, Wormhole, etc. In this paper, we have provided an analysis of the layered IoT architecture. A detailed study of different types of Jamming attacks, in a wireless sensor network, is presented. The packet loss rate, energy consumption, etc. are calculated, and the performance analysis of the WSN system is achieved. The protocol chosen to evaluate the performance of the WSN is the S-MAC protocol. Different simulations are realized to evaluate the performance of a network attacked by the different types of Jamming attacks.